Genetic Conservation and Improvement Work of Bamboos at Rain Forest Research Institute, Jorhat, Assam - Pathak, K. C.; Sarma, A. K.; Hazarika, P. K.; Neog, D.; Mishra, H. (Indian Forester, 2005)
To meet the increasing demand of bamboos for industrial and other uses it is necessary to develop a standardized methodology for selecting plus clumps leading to effective genetic improvement. This has been attempted for some species e.g. Bambusa balcooa, B. bambos, B. nutans, B. pallida, B. tulda and Dendrocalamus hamiltonii. There is need for further investigations to study behaviour, vegetative multiplication of the plus clumps. The growth index for selection is given. Performance trials are in progress.